Green credit and enterprise green operation: Based on the perspective of enterprise green transformation - Niu, Haiyan; Zhao, Xiongfei; Luo, Zhilin; Gong, Yuxia; Zhang, Xinhua (Frontiers in Psychology, 2022)
This paper uses panel data of listed heavily polluting enterprises from 2007 to 2021, based on the perspective of transformation and upgrading of heavy polluters, innovatively studies the impact of green credit on the green operation of enterprises. At the micro level, the research results of this paper verify the effectiveness of green credit policy on the transformation of green enterprises. It is also found that the two intermediary paths of debt cost and government subsidy play a partial intermediary role in the process of green credit promoting green enterprise transformation and upgrading. Green credit policy also moderates the green transformation of enterprises through debt cost and government subsidies. Based on the research results, this paper puts forward targeted policy suggestions from the aspects of financing constraints, government subsidy policies, enterprise technological innovation and green operation, and provides empirical support for the current expansion of green credit policies in China.